Sistem Pakar Mendeteksi Kondisi Kesehatan Mental Dengan Metode Forward Chaining Berbasis Android - Rima Tamara Aldisa (JURIKOM (Jurnal Riset Komputer), 2022)
The Expert System here is a system designed or built to imitate an expert using Android that can be installed, this system helps in handling and providing tips and solutions for these mental health conditions. From the research carried out, an Android-based expert system for the diagnosis of mental health conditions using the forward chaining method can provide information about 3 types of mental health, 15 symptom data, 3 different types of mental health, provide information about causes and tips on maintaining health conditions. mental health, to suggestions for final treatment. The results of the test using the Alpha Test on 17 respondents who we directed to install the expert system application first, the respondents consisted of students and the general public obtained the answer "Correct" has a percentage value of 0.51 or like 51%, and testing using Black Box testing that shows the value of the results according to the referral site